Tumor volume changes after stereotactic, hypofractionated and conventional radiotherapy in paragangliomas of head and neck - Paweł J. Polanowski; Agnieszka R. Kotecka‐Blicharz; Andrzej Tukiendorf; Natalia J. Amrogowicz; Aleksandra M. Nasiek; Agnieszka Pietruszka; Katarzyna M. Polanowska; Krzysztof A. Składowski (Cancer Medicine, 2024)
Abstract Background The aim of this study is comparison the effectiveness of stereotactic, hypofractionated and conventional radiotherapy assessed by the tumor volume changes of paraganglioma located in the head and neck region concerning fractional and total doses. Methods We analyzed 76 patients after radiotherapy due to paraganglioma who were assigned to 3 groups considering fractional (≤2 Gy, 3–5.5 Gy, ≥6 Gy) and total (≤20 Gy, 21–40 Gy, >40 Gy) doses. The volumes of irradiated tumors were measured and compared based on diagnostic images performed before and after the treatment. Results The mean tumor volume after the treatment with the lowest fractional dose (≤2 Gy) was decreased by 14.4 cm3. In patients treated with higher fractional doses (>2 Gy), the mean tumor volumes decreased by less than 1 cm3 for hypofractionated and stereotactic radiotherapy. 15.9 cm3 reduction of the mean tumor volume after the treatment with the highest RT total dose (>40 Gy) was stated. In patients treated with total doses ≤20 Gy and 21–40 Gy, the mean tumor volume was stable and reduced by 1.15 cm3, respectively. The analysis demonstrates a statistically significant (p < 0.05) treatment advantage in patients after the lowest fractional and highest total doses. Conclusion The reduction of the tumor's volume was reported after conventional and unconventional radiotherapy. The most significant depletion of the paraganglioma volume was noted after a factional dose ≤2 Gy and a total dose >40 Gy.